Pathogenic EDA Mutations in Chinese Han Families With Hypohidrotic Ectodermal Dysplasia and Genotype–Phenotype: A Correlation Analysis - Han, Yang; Wang, Xiuli; Zheng, Liyun; Zhu, Tingting; Li, Yuwei; Hong, Jiaqi; Xu, Congcong; Wang, Peiguang; Gao, Min (Frontiers in Genetics, 2020)
Abstract Background: This study aimed to investigate the genetic causes of hypohidrotic ectodermal dysplasia (HED) in two families and elucidate the molecular pathogenesis of HED in Chinese Han patients. Methods: Whole-exome sequencing (WES) was used to screen HED-related genes in two family members, followed by confirmatory Sanger sequencing. Bioinformatics analysis was performed for the mutations. We reviewed HED-related articles in PubMed. χ2- and Fisher’s tests were used to analyze the genotype–phenotype correlations. Results: (1) WES identified EDA missense mutations (c.1127 C>T [p.T376M; NM_001005609] in family 1 and an EDA nonframeshift deletion mutation (c.648_683delACCTGGTCCTCCAGGTCCTCCTGGTCCTCAAGGACC [p.216_228delPPGPPGPPGPQGP; NM_001005609]) in family 2. Sanger sequencing validated the results. ANNOVAR (ANNOtate VARiation) annotation indicated that c.1127 c>T was a deleterious mutation. (2) The review of published papers revealed 68 novel mutations related to HED: 57 (83.8%) were EDA mutations, 8 (11.8%) were EDAR mutations, 2 (2.9%) were EDARADD mutations, 1 (1.5%) was a WNT10A mutation, 31 (45.6%) were missense mutations, 23 (33.8%) were deletion mutations, and 1 (1.5%) was an indel. Genotype–phenotype correlation analysis revealed that patients with EDA missense mutations had a higher frequency of hypohidrosis (P=0.021). Conclusions: This study identified two EDA gene mutations in two Chinese Han HED families and provides a foundation for genetic diagnosis and counseling.